Fragmentasi Tata Kelola Regional: Analisis Kompleksitas Rezim dalam Pekerja Migran Profesional di ASEAN - Pratama, Tubagus Rizkiawan; Virgianita, Asra (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2025)
The establishment of the ASEAN Economic Community (AEC) has introduced two key instruments for regional development: the Mutual Recognition Arrangements (MRAs), which facilitate the mobility of professional migrant workers, and the ASEAN Consensus on the Protection and Promotion of the Rights of Migrant Workers, which aims to safeguard migrant workers’ rights. Despite their shared relevance, these frameworks have evolved along separate policy tracks, lacking normative and institutional integration. Drawing on Raustiala and Victor’s concept of regime complexity, this article analyzes the underlying reasons for ASEAN’s inability to harmonize the two regimes. Employing a qualitative descriptive method and utilizing both primary and secondary sources including official reports, academic journals, and credible news outlets, the study identifies three core factors: overlapping mandates, the absence of hierarchical structure within ASEAN institutions, and systemic effects between regimes. These dynamics have led to fragmented governance between sending and receiving countries, resulting in a legal protection gap for professional migrant workers. The findings suggest that the lack of coordination between MRAs and the ASEAN Consensus threatens the AEC’s vision of inclusive and equitable regional integration.